(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the significance of serum ferritin level in Pakistani diabetic population with or without retinopathy and its association with glycemic control. Study Design: Cross-sectional Place and Duration of Study: This study was conducted at the Department of Hematology, Shaikh Zayed Hospital, Lahore from January 2015 to June 2015. Materials and Methods: Twenty one normal healthy controls and 42 known diabetics of disease duration more than five years (21 without retinopathy and 21 with retinopathy) were included. All were tested for serum ferritin and Hb A1c levels. Results: Ferritin levels were found to be higher in diabetic groups as compared to normal control group. Both diabetic groups with or without retinopathy had significantly higher levels of HbA1c as compared to normal controls. Higher serum ferritin levels were observed with longer duration of diabetes. Conclusion: Ferritin levels are higher in diabetic groups with and without retinopathy as compared to controls and correlated with poor glycemic control.